2016
DOI: 10.1177/1049909115604140
|View full text |Cite
|
Sign up to set email alerts
|

Dying With Dyspnea in the Hospital

Abstract: These findings support that previous work noting many patients experience dyspnea at end of life. Despite national guidelines, health care providers may still be underrecognizing and likely not optimally treating dyspnea at the end of life in the hospital. Collaboration with palliative medicine providers may improve assessments and treatments for quality end-of-life care for hospitalized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Despite the immense resources devoted to the monitoring and care of ICU patients, the relatively high prevalence of this marker of distress during the transition to comfort measures is surprising but consistent with prior estimates. 30,67 A small study of 32 terminally extubated patients in a neurologic ICU reported a 59% rate of labored breathing. 30 Apart from the small sample size of the study, the assessment of labored breathing is not fully standardized and may have led to biased estimates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the immense resources devoted to the monitoring and care of ICU patients, the relatively high prevalence of this marker of distress during the transition to comfort measures is surprising but consistent with prior estimates. 30,67 A small study of 32 terminally extubated patients in a neurologic ICU reported a 59% rate of labored breathing. 30 Apart from the small sample size of the study, the assessment of labored breathing is not fully standardized and may have led to biased estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Others have estimated dyspnea rates of 34% among terminally extubated patients. 30,67 Previous evaluations of the use of anticipatory dosing of opiates in the setting of PVW have yielded unclear results. Two studies found that anticipatory dosing was not associated with earlier time to death, but the investigators did not examine symptom control or compare it with reactive dosing.…”
Section: Discussionmentioning
confidence: 99%
“…Morris and Galicia-Castillo 20 reported that, despite national guidelines, health-care providers still do not recognize dyspnea and do not optimally treat dyspnea in the final 24 hours of life, and few orders described treatment specifically for dyspnea. This report also demonstrated that patients with palliative care consultations more often received opioids, and opioid orders more specified treatment of dyspnea at the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with advanced COPD or ILD typically suffer from severe dyspnea, [1][2][3] which increases with approaching death and is associated with impaired quality of life. [4][5][6] In addition to dyspnea, patients with COPD and ILD suffer frequently from other symptoms, such as fatigue, weight loss, depression and anxiety, further impairing their quality of life. [7] Centers managing chronic respiratory insu ciency in patients with COPD or ILD commonly screen for dyspnea as a target of therapy.…”
Section: Introductionmentioning
confidence: 99%